Construction of a numerical groundwater flow model in areas of intense mine drainage, as exemplified by the Olkusz Zinc and Lead Ore Mining Area in southwest Poland - Juśko, Kamil; Motyka, Jacek; d’Obyrn, Kajetan; Adamczyk, Zbigniew (Geologos, 2018)
Areas of intense mine drainage that are subjected to numerical modelling require the construction of a complex model structure that will properly reflect actual conditions. This paper presents the process and results of constructing such a structure for the Olkusz Zinc and Lead Ore Mining Area, an area situated in a cone of depression the extent of which reaches 500 km2. This size range calls for a selection of appropriate external boundaries, properly separated from these of the mine drainage area. The complex geological structure of the Olkusz area, associated with considerable variation in the thickness of rock formations, discontinuities of rock levels and occurrence of numerous faults, must be schematised so that calculation layers can be identified. The faults in the study area have to be reflected in the regional model structure, although only those faults that actually affect groundwater flows should be selected. The model structure needs to include detailed recognition and reflection of hydraulic contacts between aquifer levels, together with a selection of hydrogeological parameters that are different for particular formations. Only a complex structure built in such a manner may be the foundation of further model studies.